Linguistic Construction of Women: A Feminist Stylistic Study of Aysha Baqir’s Beyond the Fields - Shakoor, Abdul; Ajmal, Muhammad; Ghazanfar, Shaista (Annals of Human and Social Sciences, 2023)
The study aims at investigating how stylistic features and linguistic choices contribute to the representation of women in the narrative. The present study highlights the issues of gender based discrimination and violence by analyzing Beyond the Fields by Ayesha Baqir through feminist stylistic perspective. It is a gripping tale of quest for justice, in which Zara, the narrator of the novel, embarks on a perilous journey to rescue her twin sister. This research is designed to analyze her struggle under the theoretical framework of Sara Mills’ (1995). The study also delves into the utilization of linguistic devices, exploring how they either challenge or reinforce gender stereotypes. The findings of the study reveal the intersection of these choices with broader sociocultural and feminist discourses. Through feminist stylistics, the dimensions of gender representation are interrogated, contributing to the ongoing conversation about the role language plays in perpetuating or subverting gender norms.